INVESTIGATE GENETIC RELATION AMONG WATERMELON CULTIVARS USING MOLECULAR DNA MARKERS - Elias, M. S.; Al-Jubouri, Kadhim D.H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to investigate genetic relation among 21 selective of watermelon seeds which collected from different commercial companies for different origins and produced at different years by using 12 primers for Inter Simple Sequence Repeat (ISSR). The results showed that the selective of Crimson sweet had genotypes highest genetic relation between ( K1 and K2) it was found less than the genetic similarity between ( K1and K4) , ( K2 and K4) .The four selective were divided two groups A and B. The results showed that the selective a Charleston gray had the highest genetic relation between (CH4 and CH6) while it found less than the genetic relation between (CH5 and CH9). The ten selectives were divided two cluster A and B,The groups A was divided three sub clusters .The results revealed that the highest genetic relation between the selective of the variety Sugar baby (S1and  S3). While found less genetic relation between the (S1 and S5) and divided the selectives of Sugar baby into two main cluster A and B, The cluster B was divided two sub cluster. The result found that the highest genetic relation among the 21 selective it was between ( CH4 and CH6), while found less than  of genetic similarity among ( CH8 and  S5) ( CH8 and S2),( S2 and K1) ,( S2 and K2) ,( S2  and CH9),( K1  and S5) ( S5 and CH9). The 21 selectives was divided two main clusters A and B the group A was divided to three sub clusters while the group B was divided two sub clusters. It could be concluded that the genetic relation it is very important in the hybridization programs to it prove a large genetic base to benefit of plant breeding programs.